Hybrid Threats and the Law of the Sea Use of Force and Discriminatory Navigational Restrictions in Straits - Lott, Alexander (Brill, 2022)
Hybrid Threats and the Law of the Sea debates the practice of states that have resorted to discriminatory navigational restrictions or aggression against foreign ships and aircraft in densely navigated straits. The book explores both widely acknowledged and lesser-known maritime incidents that meet the characteristics of hybrid warfare or hybrid conflict. This research approaches hybrid threats from the perspective of the interrelationship between navigational restrictions, law enforcement, armed attack, and the legal regime of straits. It provides guidance for determining whether the rules of armed conflict or law enforcement are applicable to various naval incidents.